The Significance of Partnership and Collaboration During Crisis: The Case of Humanitarian Intervention in Papua - Dwijayani, Rista Herjani; Muhammad, Ali (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Various types of conflicts and violence that occur in Papua Land, Indonesia, have attracted a lot of attention from the international community to participate in providing assistance and creating stability in conflict areas. Unfortunately, intervention from outside is often considered to use military force and violate the concept of sovereignty of a country. This study uses qualitative descriptive methods to analyze the international communityâ€™s strategy in conducting humanitarian interventions in Papua Land, Indonesia, since the region experienced an escalation in 2008. The results show that while in conflict areas, INGO such as the ICRC, as one of the organizations that is neutral and has no internal interest, collaborates with local security forces, such as POLRI and TNI, as well as local NGO, such as PMI to carry out humanitarian interventions in the form of (1) distributing water, food, clothing, medical equipment, and medicines. (2) Carry out COVID-19 vaccination programs and cataract surgery. (3) Conducting seminars related to law enforcement based on international standards and norms. (4) Joining the â€œNilai Kemanusiaanâ€ program (humanitarian value program), (5) holding a special meeting to sign the MoU regarding the implementation of the â€œHumanitarian Pauseâ€.Berbagai macam konflik dan kekerasan yang terjadi di Tanah Papua, Indonesia telah menarik banyak perhatian dari komunitas internasional untuk ikut serta dalam memberikan bantuan dan menciptakan stabilitas di wilayah konflik. Namun sayangnya, intervensi dari pihak luar seringkali dianggap menggunakan kekuatan militer dan melanggar konsep kedaulatan sebuah negara. Penelitian ini menggunakan metode deskriptif kualitatif untuk menganalisis strategi komunitas internasional dalam melakukan intervensi kemanusiaan di Tanah Papua, Indonesia sejak wilayah tersebut mengalami eskalasi pada tahun 2008. Hasil dari penelitian menunjukkan bahwa selama berada di wilayah konflik, INGO seperti ICRC sebagai salah satu organisasi yang bersikap netral dan tidak memiliki kepentingan internal melakukan kolaborasi dengan aparat keamanan setempat, seperti POLRI dan TNI serta NGO local, seperti PMI untuk melakukan intervensi kemanusiaan berupa: (1) mendistribusikan air bersih, makanan, pakaian, perlengakapan medis dan obat-obatan. (2) Melaksanakan program vaksinasi COVID-19 dan operasi katarak. (3) Mengadakan seminar terkait penegakan hukum berdasarkan standar dan norma internasional. (4) Bergabung dalam program â€œNilai Kemanusiaanâ€, (5) bahkan komunitas internasional mengupayakan penandatangan MoU untuk melaksanakan â€œHumanitarian Pauseâ€.